History of domestication and spread of Aedes aegypti - A Review - Powell, Jeffrey R; Tabachnick, Walter J (Memórias do Instituto Oswaldo Cruz, 2013)
The adaptation of insect vectors of human diseases to breed in human habitats (domestication) is one of the most important phenomena in medical entomology. Considerable data are available on the vector mosquito Aedes aegypti in this regard and here we integrate the available information including genetics, behaviour, morphology, ecology and biogeography of the mosquito, with human history. We emphasise the tremendous amount of variation possessed by Ae. aegypti for virtually all traits considered. Typological thinking needs to be abandoned to reach a realistic and comprehensive understanding of this important vector of yellow fever, dengue and Chikungunya.